INFORMATION GAP: DEMAND SUPPLY ENVIRONMENTAL DISCLOSURE DI INDONESIA - Djoko Suhardjanto; Umi Choiriyah (University of Merdeka Malang, 2010)
The purposes of this study were to invest igate informat ion gap of environmentaldisclosure in Indonesian and to examine relat ionship between company characterist ics andits environmental disclosures. Company characterist ics were ident if ied as size, prof itability,leverage, prof ile, and companys operat ion territory. This study also examined proport ion ofindependent commissioner and the educat ional background of commissioner president ascont rol variable. Primary and secondary data were used in this research. Interview and questionnaire to 50 respondents as broader stakeholders were used as primary data. On average,there was high demand f rom respondents on environmental disclosure (score of 3.95 within5 Likert scale). Under purposive sampling, 100 annual reports of companies in BEI were selectedas secondary data. There was 44% of those disclosed environmental informat ion. Underweighted index, the level of disclosure was 4.84%. High demand f rom broader stakeholdersto disclose environmental informat ion does not supply properly by Indonesian companies.Thus, there was informat ion gap in environmetal disclosure. Result of logist ic regressionshowed that the determinants for Indonesian companies to disclosure environmentalinformat ion were Prof itabilit y; Leverage and Proport ion of Independent Commissioner. Inaddit ion, the signif icant predictors for the level of disclosure were Leverage; Proport ion ofIndependent Commissioner and the Educat ional Background of Commissioner President .